2014
DOI: 10.1093/ecco-jcc/jju018
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Early Infliximab Response in Crohn's Disease: a Meta-analysis

Abstract: Though smoking worsens CD, this meta-analysis does not show a negative effect of smoking on initial response to infliximab. This must be viewed in the proper context, as long-term maintenance of response may yet be influenced by smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…However further data supporting a detrimental impact on treatment outcomes per se are surprisingly sparse. For instance, 2 large meta-analyses were unable to depict an effect of smoking status on response to infliximab, 22,23 and smoking, if anything, may have a positive impact on thiopurine metabolism and related treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However further data supporting a detrimental impact on treatment outcomes per se are surprisingly sparse. For instance, 2 large meta-analyses were unable to depict an effect of smoking status on response to infliximab, 22,23 and smoking, if anything, may have a positive impact on thiopurine metabolism and related treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of these showed no difference in response and relapse rates for both luminal and fistulizing CD although the remaining 2 studies demonstrated that smokers had reduced early response rates and shorter time to relapse. Also, a more recent meta-analysis examining the impact of smoking on early response to infliximab by Inamdar et al 23 www.irjournal.org analyzed 8 studies, comprising 1,658 patients. Most were prospective studies and assessed both luminal and fistulizing CD.…”
Section: Anti-tnf Agentsmentioning
confidence: 99%
“…In addition, a recursive search identified other potentially eligible studies among the bibliographies of selected articles. Finally, we searched the bibliographies of previous systematic reviews in this area . Eligibility was judged by two independent investigators with any disagreements resolved by a third investigator.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we searched the bibliographies of previous systematic reviews in this area. [18][19][20][21][22][23][24][25] Eligibility was judged by two independent investigators with any disagreements resolved by a third investigator.…”
Section: Methodsmentioning
confidence: 99%
“…Smokers with CD have a more complicated disease course and discontinuation led to better outcomes ( 32 34 ). Although, some studies have indicated worse outcomes of anti-TNF treated smoking CD patients in comparison to non-smokers ( 35 , 36 ), two meta-analyses found no effect of smoking on primary effectiveness of infliximab in CD patients ( 37 , 38 ). In UC, smokers have reduced colectomy rates, less primary sclerosing cholangitis and less back-wash ileitis than never smokers ( 39 ).…”
Section: Patient and Disease Related Predictors To Anti-tnf Therapymentioning
confidence: 99%